Cell‐laden biphasic scaffolds with anisotropic structure for the regeneration of osteochondral tissue. (18th March 2014) - Schütz, Kathleen; Despang, Florian; Lode, Anja; Gelinsky, Michael
Abstract: Sufficient treatment of chondral and osteochondral defects to restore function of the respective tissue remains challenging in regenerative medicine. Biphasic scaffolds that mimic properties of bone and cartilage are appropriate to regenerate both tissues at the same time. The present study describes the development of biphasic, but monolithic scaffolds based on alginate, which are suitable for embedding of living cells in the chondral part. Scaffolds are fabricated under sterile and cell‐compatible conditions according to the principle of diffusion‐controlled, directed ionotropic gelation, which leads to the formation of channel‐like, parallel aligned pores, running through the whole length of the biphasic constructs. The synthesis process leads to an anisotropic structure, as it is found in many natural tissues. The two different layers of the scaffolds are characterized by different microstructure and mechanical properties which provide a suitable environment for cells to form the respective tissue. Human chondrocytes and human mesenchymal stem cells were embedded within the chondral layer of the biphasic scaffolds during hydrogel formation and their chondrogenic (re)differentiation was successfully induced. Whereas viability of non‐induced human mesenchymal stem cells decreased during culture, cell viability of human chondrocytes and chondrogenically induced human mesenchymal stem cells remained high within the scaffolds over the whole culture period of 3 weeks, demonstrating successful fabrication of cell‐laden centimetre‐scaled constructs for potential application in regenerative treatment of osteochondral defects. Copyright © 2014 John Wiley & Sons, Ltd.